Mooting And Technology: Simulations In Legal Education - Abdul Razak, Aida; Abdul Rahim, Asmar; Badarulzaman, Muhammad Hafiz; Md Nasir, Nor Ashikin (2022)
This article considers how law schools can facilitate the development of technology skiffs by using technology to enhance access to mooting in settings that replicate legal practice. It examines the experiential learning technique of simulation, particularly the use of moot courts and mock trials, in the context of legal education. It provides an overview of extant literature along with an outline of the current place of simulation activities in Malaysian legal education (particularly in Universiti Utara Malaysia) and examining the efficacy of simulation activities as a teaching and learning tool. This article provides a strategy for law schools to incorporate electronic technology into the curriculum to better achieve the goals of legal education in the 21st century. The paper concludes that while it is essential to teach technology skiffs as part of legal education, it is important that the benefits of using technology are made clear in order for it to be accepted and embraced by the students. Technology must also be available to aff students considering the widening participation in higher education and consequent increasing diversity of law students.